PENGARUH PERMAINAN TRADISIONAL DALAM PEMBELAJARAN PENJAS DI SEKOLAH DASAR TERHADAP PENGEMBANGAN GERAK DASAR DAN SELF ESTEEM - Santosa, Agus (STKIP Pasundan, 2016)
The purpose of this study was to determine the effect of traditional games and conventional learning in physical education learning in elementary schools on the development of basic motion and self esteem. The research method uses an experimental method with Randomize Pretest-Posttest Control Group Design. The population of this research is grade IV students of Garuda Bandung Elementary School consisting of five classes A, B, C, D and E. The sampling technique uses cluster random sampling with random selection that is selecting from five classes A, B, C, D and E and obtained two Classes are Class C and D, then random assignment is carried out so that the experimental group class is D class and the control group is Class C with each class there are 30 research samples. The instrument in this study used motor abilities and self esteem questionnaires. The results show that, 1) There is a significant influence of traditional games in Physical Education learning in elementary schools on the development of basic motion; 2) There is a significant influence of traditional games in the learning of Physical Education in elementary school on the development of self esteem; 3) There is a significant influence of conventional learning in physical education learning in elementary schools on the development of basic motion; 4) There is a significant influence of conventional learning in physical education learning in elementary schools on the development of self esteem; 5) There is a difference in the influence of traditional games with conventional learning in physical education learning in elementary schools on the development of basic motion and self esteem.